2021
DOI: 10.3399/bjgpo.2021.0132
|View full text |Cite
|
Sign up to set email alerts
|

Medication prescribing in face-to-face versus telehealth consultations during the COVID-19 pandemic in Australian general practice: a retrospective observational study

Abstract: BackgroundThere has been a precipitous rise telehealth use in general practice during the COVID-19 pandemic. Understanding differences between face-to-face and telehealth consulting is an important component for planning the future use of telehealth services beyond the pandemic. However, there is limited evidence on whether telehealth consulting impacts medication prescribing under pandemic circumstances.AimTo compare medication prescribing in face-to-face versus telehealth consultations during the COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Another study revealed that fewer medications were prescribed during telehealth consultations than in-person consults. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that fewer medications were prescribed during telehealth consultations than in-person consults. 9 …”
Section: Introductionmentioning
confidence: 99%
“…, 29. , 30. A number of rapid and significant changes in the use of technology for patient care occurred during the COVID-19 pandemic, and while many have shown good acceptability among patients and healthcare professionals, the long-term impact on patient care is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…During the coronavirus disease (COVID-19) pandemic, the mode of consultation of the patients has also switched to online in substitute to in-person consultation [ 24 ]. Patients have been looking for an alternative to face-to-face consultation, and online as well as telecommunication-based consultations are in practice [ [25] , [26] , [27] ]. More than half of the responders disregarded online consultation as a substitute for in-person consultation with the physician.…”
Section: Discussionmentioning
confidence: 99%